Microsatellite variability of sulfonylurea‐resistant and susceptible populations of Schoenoplectus juncoides (Cyperaceae) in Kinki, Japan. (30th September 2013) - Yamada, Y; Tominaga, T; Ohsako, T; Darmency, Henri
Summary Schoenoplectus juncoides is one of the most harmful weeds found in East Asian paddy fields. Recent emergence of biotypes that are resistant to the herbicide sulfonylurea (SU) has made weed control difficult. To examine the effect of the evolution of this herbicide resistance on genetic diversity within local populations, we investigated microsatellite variability within and among paddy field populations of S. juncoides in Kinki, Japan. In vivo assay of acetolactate synthase activity and root elongation assay in the presence of SU revealed that of 21 populations, five were sulfonylurea‐susceptible (SU‐S) and eight were completely sulfonylurea‐resistant (SU‐R). The remaining eight populations were a mixture of SU‐S and SU‐R individuals. The average gene diversity for SU‐R populations (HS = 0.168) was lower than those for SU‐S (HS = 0.256) and mixed (HS = 0.209) populations, but the difference was not significant. This indicates that positive selection for SU‐R phenotype did not cause a genome‐wide reduction in genetic diversity. Genetic differentiation among S. juncoides populations was higher than that observed for most weed species studied previously. Although populations in neighbouring paddy fields showed a high level of differentiation, Bayesian clustering analyses suggested that some level of gene flow occurs among them and that the genetic exchange or colonisation between neighbouring populations could contribute to the geographical expansion of the resistant allele.